GEOCHEMICAL AND SCLEROCHRONOLOGICAL ANALYSES OF THE LOWER PLEISTOCENE MACROFAUNA OF WESTERN EMILIA (NORTHERN ITALY): PALAEOENVIRONMENTAL AND PALAEOCLIMATIC IMPLICATIONS - G. Crippa (Università degli Studi di Milano, 2015)
The Early Pleistocene is a time interval characterized by several climatic oscillations which has its lower and upper boundaries coinciding respectively with the beginning of the Northern Hemisphere Glaciation and the Middle Pleistocene Transition. The Mediterranean area was strongly affected by the Early Pleistocene climatic changes. One of the most important biotic event is here represented by the appearance of the boreal guests (e.g. the bivalve Arctica islandica and the foraminifer Hyalinea balthica) at the beginning of the Calabrian Stage, suggesting significant cooling of the Mediterranean Sea, which is also confirmed by a change in the pollen flora indicating cold climatic conditions. The Arda River marine succession, cropping out in Western Emilia, Northern Italy, is very rich in macrofossils and it covers without significant gaps the Early Pleistocene. It thus represents an ideal setting where to study the climatic oscillations of this time interval. This study, combining sedimentology, taxonomy, palaeoecology, biostratigraphy and geochemistry and sclerochemistry of bivalve shells, provides an integrated investigation of the palaeoenvironmental and palaeoclimatic conditions accompanying these major climatic changes in the Arda section. The Arda marine succession is 237.40 m-thick and consists of sandstones, siltstones and mudstones deposited in a tectonically active setting during phases of advance of fan deltas; it is bounded at the top by continental conglomerates indicating a major sea level drop and the establishment of a continental environment with vertebrate faunas and fresh water mollusks. The taxonomic analysis of the macrofauna allows to identify 159 taxa, of which bivalves are dominant with 105 taxa, followed by gastropods (44 taxa) and a few corals (3 taxa) and serpulids (2 taxa); brachiopods, echinoids, barnacles, bryozoans and scaphopods do also occur. The comparative sedimentological and palaeoecological analysis shows that the Arda marine succession deposited in an infralittoral to a ...